UJI EFEKTIVITAS EKSTRAK KULIT BUAH MANGGIS (GARCINIA MANGOSTANA) SEBAGAI ALTERNATIF ANTIBAKTERI TERHADAP ESCHERICHIA COLI SECARA IN VITRO - ., Yulianty; Deasy, Astrid; AS, Noorhamdani; Soemantri, Bambang (Jurusan Kedokteran FK Unsoed, 2013)
At this time trend back to nature has increased the use of medicinal plants because they are easily to get, cheap, safely enough and effective. One of medicinal plants is mangosteen (Garcinia mangostana) which the rindâs part is often used as alternative medicine of diarrhea. Epidemiological study showed that Escherichia coli was a major cause of acute diarrheal besides Shigella, Salmonela, Vibrio and Campylobacter sp. Escherichia coli cause approximately 25% of prevalence of acute diarrheal. The resistance of Escherichia coli to synthetic antibacterial has increase over 2-3 times so it needed an alternative antibacterial. The main aim of this experimental research was to discover the effect of mangosteenâs rind extract as antibacterial to Escherichia coli with in vitro method. The specific aims were to discover the effect of extract concentrations to the growth of colony and to find MIC (Minimum Inhibitory Concentration) and MBC (Minimum Bactericide Concentration). Method that used in this research was Tube Dilution Test. The concentrations that used in this research were 2%, 3%, 4%, 5% and 6% with 0% concentration as positive control and 100% concentration as negative control. The experiment was repeated for 4 times. Statistic analysis was found that there is different between colony growth with extract concentrations significantly (One-way ANOVA, p<0,000). Analysis of Correlation Test was found a strong relation with negative direction (r= -0,932) that higher concentration of extract therefore lower colony growth. Analysis of Linear Regression Test was found determination value (R square) 86,8% with the equation Y=33616,071â6651,071X. MIC value in this research was could not be determined whereas MBC value could be determined at 5% concentration. Therefore, it was concluded that mangosteenâs rind extract is effective as antibacterial to Escherichia coli with in vitro method.